Optimalisasi biaya produksi dan peningkatan laba melalui analisis biaya volume dan laba pada Dolphin Bakery - Katemba, Destiana; Sabijono, Harijanto; Mintalangi, Syermi S. E. (Yayasan Widyantara Nawasena Raharja, 2024)
Cost Volume Profit analysis (CVP) is a technique or tool that provides an unparalleled understanding of a company's costs, sales volume, and profit earned over a certain period. It does this by offering a clear explanation of the relationship between a company's costs, volume, and profit. This study will determine how production costs can be optimized and profits increased through the analysis of volume costs and profits in Dolphin Bakery. This study employs a qualitative descriptive research method. The results demonstrate that the contribution margin has exceeded fixed costs, significantly contributing to the company's profit. The break-even point indicates that revenue has exceeded the point of no profit and loss, while the margin of safety shows that the maximum number of sales is safe. These findings highlight the necessity for effective planning and pricing strategies to achieve higher profit targets.